Sedimentological and geochemical aspects of an Amazon estuary: the Sucuriju River estuary, Amapá, Brazil - Xavier, Diego de Arruda; dos Reis, Caio Daniel Nascimento; da Silva, José Francisco Berrêdo Reis (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
The study aims to analyze the Sucuriju estuary through sedimentological, geochemical and physical-chemistry parameters, in support of a vulnerability study of environmental risk of a possible oil spill accident in the Cabo Norte region, Amapá, Brazil. Sixty-six samples of surface sediment were employed for grain size percentage characteristics; total organic carbon, total nitrogen and total phosphorus concentrations; salinity, pH, and redox potential in interstitial sediments. The fraction percentages showed for sand an average of 19.51 ± 13.44%, silt 72.50 ± 11.17%, and clay 7.98 ± 4.49%. Salinity, pH, and redox potential registered averages of 20.76 ± 2.59, 7.20 ± 0.26, and 192.32 ± 129.96 mV, respectively. The organic carbon, total nitrogen, total phosphorus, and C/N ratios registered averages of 1.34 ± 0.71 g.kg-1, 0.38 ± 0.23 g.kg-1, 103.93 ± 63.89 g.kg-1 and 4.45 ± 3.96, respectively. The sedimentary and geochemistry characteristics showed for the Sucuriju estuary, added with hydrodynamic and climatic processes determine a possible high vulnerability of a possible oil spill incident in the Amapá coastal system. This result will serve as a base for the elaboration of mitigation plans for these events.